2017
DOI: 10.1111/ajt.14089
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Supply of Liver Segment IV and Its Possible Surgical Consequences

Abstract: The risk of ischemia of segment IV after split liver resection is high. This anatomical study was done to identify the arterial blood supply and the intrahepatic distribution of liver segment IV. The anatomy of segment IV was studied in 29 livers from adult cadavers. To identify the arterial blood supply of segment IV, water and ink were injected into the various branches of the hepatic artery and the outflow through segment IV and discoloration of the liver parenchyma were observed. In 23 of the 29 livers (79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
19
1
6
Order By: Relevance
“…The levels of ALT and AST were significant higher in ERL recipients in the early postoperative days. One of the concerns of using ERL was the viability of segment IV because the lack of blood supply in segment IV may affect liver function . The ischemic changes in segment IV may cause hepatocyte necrosis and induce the transient release of ALT and AST; this is why the difference was seen in ALT and AST but not in TBIL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of ALT and AST were significant higher in ERL recipients in the early postoperative days. One of the concerns of using ERL was the viability of segment IV because the lack of blood supply in segment IV may affect liver function . The ischemic changes in segment IV may cause hepatocyte necrosis and induce the transient release of ALT and AST; this is why the difference was seen in ALT and AST but not in TBIL.…”
Section: Discussionmentioning
confidence: 99%
“…One of the concerns of using ERL was the viability of segment IV because the lack of blood supply in segment IV may affect liver function. 21 showing that the ischemic changes in segment IV did not influence recipient outcomes after SLT. 22 We chose 3 months after transplant as the cut-off point to evaluate the short-term outcomes because most of the surgeryrelated or life-threatening complications occur within 3 months after surgery.…”
Section: Infectionmentioning
confidence: 92%
“…Arterial irrigation of the liver. Bianchi et al (2014), Rachanee Chanasong (2014), Dandekar et al (2015), Yan et al (2015), Durand-LĂłpez (2016) and Alghamdi et al (2017) found: Arterial irrigation comes from the hepatic artery proper in 70 % of cases; from the hepatic artery proper and a branch of left gastric artery (A12.2.12.013) in 25 %, from the hepatic artery proper plus a branch from left gastric artery plus a branch from superior mesenteric artery (A12.2.12.053) in 3 %, and from the hepatic artery proper and a branch from superior mesenteric artery in 2 %. The hepatic artery proper is divided into left and right branches; the left branch is short and less voluminous than the right branch.…”
Section: Resultsmentioning
confidence: 99%
“…As for the putative functions of each cell type, we were surprised to find that the Endo-DNTT cell type showed immune-related functions ( Figure S3E) despite little PTPRC (CD45) expression. Although most of the cell types showed similar composition in different positions, the fraction of erythrocytes declined from segment IV to around regions (segment VII/VI/II/III) ( Figure S3F), highlighting the important roles of blood supply in the segment IV (Alghamdi et al, 2017).…”
Section: Construction Of the Single-cell Transcriptome Landscape For mentioning
confidence: 99%